The Influence of Using Sundanese Dialect on the Indonesian Language in the Pandeglang Community - Ari Fajria Novari; Ifa Najilah (Journal of English Education Studies, 2026)
Sundanese is a regional language that is the first language for the people of Pandeglang. It is undeniable that many people use Sundanese in various aspects of life, including when communicating with others and even in education. Nowadays, there are many phenomena of code mixing between Sundanese and Indonesian, where Indonesian is the national language. Indonesian country. Not a few people argue that the occurrence of code mixing between the use of Sundanese and Indonesian is considered to have an impact on the preservation of the Indonesian language. Therefore, researchers need to conduct research with the aim of finding out the reasons for code mixing between the use of language and the use of Indonesian. The result of the study indicates that some people use Indonesian, and there is code mixing in its use. The language that emerged was Sundanese because it is used and preserved by some speaker-. In the use of Indonesian people should know the correct use of Indonesian, both formal and non-formal forms, so that there are no variations in language in the context of interacting and communicating. This research was conducted based on the experiences encountered and experienced by the writer.